The Potential Role of Epigenetic Mechanisms in the Development of Retinitis Pigmentosa and Related Photoreceptor Dystrophies - Dvoriantchikova, Galina; Lypka, Karin Rose; Ivanov, Dmitry (Frontiers in Genetics, 2022)
Retinitis pigmentosa and related photoreceptor dystrophies (RPRPD) are rare retinal diseases caused by hereditary gene mutations resulting in photoreceptor death, followed by vision loss. While numerous genes involved in these diseases have been identified, many cases have still not been associated with any gene, indicating that new mechanisms may be involved in the pathogenesis of these photoreceptor dystrophies. Many genes associated with RPRPD regulate photoreceptor specification and maturation in the developing retina. Since retinal development begins with a population of equivalent, proliferating retinal progenitor cells (RPCs) having a specific “competence” in generating all types of retinal neurons, including cone and rod photoreceptors, we tested the epigenetic changes in promoters of genes required for photoreceptor development and genes associated with RPRPD during RPC differentiation into cone and rod photoreceptors. We found that promoters of many of these genes are epigenetically repressed in RPCs but have no epigenetic restrictions in photoreceptors. Our findings also suggest that DNA methylation as an epigenetic mark, and DNA demethylation as a process, are more important than other epigenetic marks or mechanisms in the pathogenesis of these diseases. Most notably, irregularities in the DNA demethylation process during the RPC-to-photoreceptor transition may significantly contribute to retinitis pigmentosa (RP) pathogenesis since genes with hypermethylated promoters in RPCs account for at least 40% of autosomal recessive RP cases and at least 30% of autosomal dominant RP cases. Thus, we proposed an epigenetic model according to which unsuccessful demethylation of regulatory sequences (e.g., promoters, enhancers) of genes required for photoreceptor development, maturation, and function during the RPC-to-photoreceptor transition may reduce or even eliminate their activity, leading to RPRPD without any inheritable mutations in these genes.